Phylogeny, Evolution, and Transmission Dynamics of Canine and Feline Coronaviruses: A Retro-Prospective Study - Yang, Hu; Peng, Qianling; Lang, Yifei; Du, SenYan; Cao, SanJie; Wu, Rui; Zhao, Qin; Huang, Xiaobo; Wen, Yiping; Lin, Juchun; Zhao, Shan; Yan, Qigui (Frontiers in Microbiology, 2022)
Canine coronavirus (CCoV) and feline coronavirus (FCoV) are endemic in companion animals. Due to their high mutation rates and tendencies of genome recombination, they pose potential threats to the public health. The molecular characteristics and genetic variation of both CCoV and FCoV have been thoroughly studied, but their origin and evolutionary dynamics still requires further assessment. In the present study, we applied a comprehensive approach and analyzed the S, M and N genes of different CCoV/FCoV isolates. DAPC and phylogenetic analysis showed the FCoV sequences from Chinese isolates were closely related to the FCoV clusters in the Netherlands, while recombination analysis indicated that of S N-terminal domain (NTD) was the most susceptible region of mutation, and recombination of this region is an important cause for the emergence of new lineages. Natural selection showed that CCoV and FCoV subgenotypes were in selection constraints, and CCoV-IIb was in strong positive selection. Phylodynamics showed that the mean evolution rate of S1 genes of CCoV and FCoV are 1.281×10-3 and 1.244×10-3 subs/site/year, and the tMRCA of CCoV and FCoV were about 1901 and 1822, respectively. Taken together, our study centered on tracing the origin of CCoV/FCoV, and provided ample insights into the phylogeny and evolution of canine and feline coronaviruses.